A Nanoparticle Catalyst for Heterogeneous Phase Para‐Hydrogen‐Induced Polarization in Water1. (7th January 2015) - Glöggler, Stefan; Grunfeld, Alexander M.; Ertas, Yavuz N.; McCormick, Jeffrey; Wagner, Shawn; Schleker, P. Philipp M.; Bouchard, Louis‐S.
Abstract Para‐hydrogen‐induced polarization (PHIP) is a technique capable of producing spin polarization at a magnitude far greater than state‐of‐the‐art magnets. A significant application of PHIP is to generate contrast agents for biomedical imaging. Clinically viable and effective contrast agents not only require high levels of polarization but heterogeneous catalysts that can be used in water to eliminate the toxicity impact. Herein, we demonstrate the use of Pt nanoparticles capped with glutathione to induce heterogeneous PHIP in water. The ligand‐inhibited surface diffusion on the nanoparticles resulted in a 1H polarization of P=0.25 % for hydroxyethyl propionate, a known contrast agent for magnetic resonance angiography. Transferring the 1H polarization to a 13C nucleus using a para‐hydrogen polarizer yielded a polarization of 0.013 %. The nuclear‐spin polarizations achieved in these experiments are the first reported to date involving heterogeneous reactions in water.